Vitamin D in Reproductive Health and Pregnancy - Mousa, Aya; Abell, Sally; Scragg, Robert; Courten, Barbora de (Seminars in Reproductive Medicine, 2016)
Vitamin D has been primarily known for its role in maintaining calcium and phosphorus homeostasis and promoting healthy bone mineralization. Emerging evidence suggests that vitamin D may have a plethora of other functions including cardiometabolic and immunological effects and a role in modulating human reproductive processes. Despite this, vitamin D deficiency (VDD) remains highly prevalent worldwide due to the limited availability of foods that are naturally high or fortified with vitamin D, increased sun avoidance behaviors and use of sunscreen due to fear of skin cancer, and increased sedentary indoor lifestyles, especially among those of reproductive age. This review examines current and emerging evidence for the role of vitamin D in reproductive health including in fertility, conception, and pregnancy outcomes, and outlines areas for future research. We found that existing evidence is based primarily on animal models and in vitro studies with some recent support from observational studies in humans. While these studies indicate that VDD may be a risk factor for adverse fertility and pregnancy outcomes, there is insufficient evidence to establish causality. Future efforts to clarify the benefits of vitamin D in reproductive health may bring about practical, simple, and cost-effective means of improving fertility and pregnancy outcomes.
Keywords: vitamin D; reproduction; fertility; pregnancy; birth; neonatal